Fatostatin in Combination with Tamoxifen Induces Synergistic Inhibition in ER-Positive Breast Cancer [Corrigendum] - Liu Y; Zhang N; Zhang H; Wang L; Duan Y; Wang X; Chen T; Liang Y; Li Y; Song X; Li C; Han D; et al. (Dove Medical Press, 2022)
Liu Y, Zhang N, Zhang H, et al. Drug Des Devel Ther. 2020;14:3535–3545. The authors have advised due to an error at the time of figure assembly, Figure 7C on page 3543 is incorrect. The correct Figure 7 is shown in Download Article.   The authors apologize for this error and advise it does not affect the results of the paper. Read the original article